Direito à proteção de dados como direito da personalidade - Pires, Mariana Ferreira da Cruz (2023)
The object of this research is to analyze the possibility of recognition of data protection as a right of personality. The dissertation began with the presentation of the importance the study of comparative law in the subject for a better understanding. After, it was done a study about the rights of personality, approaching its origins, grounds, nature, elements and the relation with the principle of human dignity. In sequence, the investigation studied the right to privacy, from the historical development, the hard task to define and delimit, the current legal system, its connection with the right to freedom and the private autonomy and the role in the informational society. However, the heart of the dissertation it was the study of the right to data protection, aiming to sustain the possibility of its recognition as a right of personality. Also, it was made a breaf examination about certain legal resources of protection of personality in the scope of data treatment. The research methodology is qualitative, bibliographic and documentary. The research is descriptive and exploratory, aiming to devolp ideas from information on the topic